Julmarichardia gutui, a new species of Apseudomorph Tanaidacean (Crustacea: Malacostraca: Peracarida) from the Australian northwest continental shelf - Ritger, Rebecca Kirk; Heard, Richard W. (Zootaxa, 2007)
Julmarichardia gutui, n. sp. is described from specimens collected in depths of 78–83 m from the Northwest Continental Shelf of Australia. Of the four previously known species of Julmarichardia Guţu, 1989, J. gutui is distinguished from J. deltoides (K. H. Barnard, 1914) and J. thomassini Guţu, 1989 by having the outer flagella of the antennule with fewer than 9 articles and its distinctive armature on anterodorsal region of the carapace. It can be separated from J. alinati Guţu, 1989 and J. bajau Bamber and Sheader, 2005 by a combination of characters, including (1) a spatulate rostrum fringed with 20 or more blunt marginal teeth interspersed with 5–8 small plumose setae; (2) distinct ridges or tubercles on the carapace, (3) a well-developed, expanded lateral lobe on article 1 of the antenna (absent in J. bajau), and (4) 3–5 blunt spines (instead of 1 or 2) on the anterior margin of the basis of pereopod 2. A key to the five nominal species now comprising the genus Julmarichardia is presented. Julmarichardia gutui represents the first record of its genus from Australian waters and the second for the genus in the eastern Indian Ocean.